Strategi keuangan di masa pandemi: Analisis Faktor-faktor yang mempengaruhi minat menabung di Bank Syariah di Kabupaten Tegal - Velayati, Maya Fauziah (Nur Science Institute, 2023)
This study analyzes factors influencing people's interest in saving in Islamic banks, especially in the Tegal Regency area, with knowledge, promotion, trust, religiosity, income, and brand awareness being the moderating variables. This study uses a quantitative approach with primary data collected through a questionnaire with a random sampling technique. The number of samples used was as many as 100 respondents, who are the people of the Tegal Regency. The analysis used moderated regression analysis. The results showed that knowledge, promotion, and income positively and significantly affected interest in saving. Trust has a negative and insignificant effect on interest in saving. Religiosity has a negative and significant effect on interest in saving. Brand awareness has a positive and significant effect on interest in saving. Meanwhile, brand awareness can only moderate the influence of religiosity and income on interest in saving. Islamic banks must continue to improve the determinants of public interest to increase the existence of Islamic banks.